Multiple Addressing Coordination and Switching Technology in Space-Integrated-Ground Information Network - Wenlan DIAO; Jianping AN; Yu ZHANG; Han HU (天地一体化信息网络)
The construction requirements and deployment status of the space-integrated-ground integrated information network was analyzed, and the diffi culties in the integration of satellite network and internet was discussed.To tackle the problems of complex network structure, high dynamic topology, diffi cult data compatibility and limited satellite resources, a multi addressing coordination and switching technology based on IP address, ID identifi cation and content name was proposed.In particular, a multi addressing datagram format was designed, and the multi addressing route forwarding mechanism was extended.It could realized the interconnection of heterogeneous networks, the stability of mobile communication, the compatible switching of polymorphic data, and the effi cient routing with low power consumption of satellites.